Challenges and Opportunities for Co-Existence: A Sri Lankan Christian Perspective - Paul Rohan, J.C. (Minhaj University, Lahore, Pakistan, 2021)
God has revealed himself in many different ways and this has given rise to various religious traditions. The principal function of religion is to be a link (re+ligare) with God. However, in the history of the world, the religions have deviated from this noble purpose. The present world order with its conflicts, violence, injustice, discrimination, anti-life concepts and unjust practices raises the fundamental question: “Are the religions contributing to human wellbeing and harmony or have they given rise to various forms of extremism and violence that will eventually destroy the world?” Sri Lanka, a small island-nation, contains four religious traditions existing side by side and, therefore, provides an opportunity to explore how interfaith dialogue and collaboration can contribute to the harmonious coexistence of a multi- religious society. This article discusses the ground reality of religious plurality in Sri Lanka and concludes that religious plurality can provide an opportunity for coexistence among religious traditions.
Keywords: Plurality; Diversity; Interreligious dialogue; Coexistence